LITERATURE OF REVIEW THE INFLUENCE OF COMMUNICATION AND WORK LOYALTY ON EMPLOYEE PERFORMANCE AT PT. MAYORA INDAH TBK - Angga Ian Saputra (Draf Solusi Indonesia, 2023)
This research is a design literature review thatexamines the influence of communication and loyaltyon employee performance. This research wasconducted at PT. Mayora Indah Tbk. This researchuses a quantitative approach as a method for solvingresearch problems using the questionnaire method.This research will use SPSS as a statistical tool used totest the feasibility of the data and draw conclusionson the hypothesis.